Reasons for adherence of incontinent elderly women after a follow-up of 24 months of muscle training Motivos de aderência das idosas incontinentes após follow-up de 24 meses de treinamento muscular - Mazo G.Z.* (2018)
© Edições Desafio Singular.Objective: to investigate the adhesion motives 24 months after intervention with training of pelvic floor muscles (PFMT) with and without bodybuilding in elderly women with urinary incontinence (UI). Method: After the 24-month follow-up of the interventions, 23 elderly women were contacted. The International Consultation on Incontinence Questionnaire (ICIQ-SF) was used to verify the frequency and severity of UI and the TMAP Practice Reasoning Questionnaire to describe the reasons for adherence to PFMT and physical exercise practice (RPA). Results: After 24 months of UI treatment through TMAP with and without bodybuilding, 30.4% (n = 7) of the elderly women remained continents. Adherence to TMAP was 52.2% (n = 12) and AFR was 73.9% (n = 17), after 24 months of intervention. The reason for the practice of PFMT was the prevention of UI. For RPA, the main reason was the improvement of general health. Conclusion: We suggest new studies that use strategies to facilitate adherence to treatment, over a long period of follow-up.